Postnatal expression of alpha2 nicotinic acetylcholine receptor subunit mRNA in developing cortex and hippocampus - Son, Jong-Hyun (2006)
Nicotinic acetylcholine receptors (nAChRs) are pentameric ligand-gated cation channels composed of α and β subunits. nAChR subunit expression is highly regulated during development. Previous studies have revealed increased expression of α3, α5, α7, and β4 subunit mRNAs and α7 binding sites during hippocampal and cortical development. Here, we examined the expression of α2 subunit mRNA in rat cortex and hippocampus using highly sensitive radioactive in situ hybridization. α2 subunit mRNA expression was first detected at P3 in cortex and hippocampus. During postnatal development the distribution of α2 subunit mRNA expression was spatially similar to the one found in adult, exhibiting highly restricted expression in scattered cells mostly in cortical layer V and retrosplenial cortex, and in scattered cells in CA1/CA3 stratum oriens and CA3 stratum radiatum. However, the expression intensity and number of α2 positive cells strongly increased to reach peak levels in both cortex and hippocampus at P7 and decreased thereafter to moderate to low to levels. Double in situ hybridization revealed that most, but not all, α2 mRNA expression was located in non-pyramidal GAD-positive cortical and hippocampal interneurons. Thus, similar to other nAChR subunits, α2 mRNA expression is transiently upregulated during postnatal development and nAChRs containing α2 subunits could regulate GABAergic activity during a critical period of network formation.